A JOURNEY TO THE CENTRE OF EARTH - Verne, Jules, 1828-1905.; Nodel, Norman (Newbury, Berkshire : CCS Books, 2019)
After discovering a note from the esteemed Icelandic scientist, Arne Saknussemm, Professor Lidenbrock and his nephew Axel undertake a dangerous and exciting adventure into the belly of the Earth!
Includes a biography of Jules Verne, theme discussions and study questions.
Primary.
Keywords: Explorers -- Comic books, strips, etc; Children's stories -- Comic books, strips, etc; Earth (Planet) -- Core -- Comic books, strips, etc; Iceland -- Comic books, strips, etc; Graphic novels; Comics adaptations